3. Lactobacillus casei Fermented Milk as a Treatment for Diabetes in Mice (Mus musculus) - Pratiwi Purnama Sari; Nurliana Nurliana; M. Hasan; Arman Sayuti; Sugito Sugito; Amiruddin Amiruddin (Universitas Syiah Kuala, 2017)
The study aimed to find out the effect of Lactobacillus casei fermented milk as diabetic drug (Therapeutic). Mice were 3-4 month old, male and body weight ranged 20-30 g. This Research used Completely Randomized Design with factorial pattern, consisted of dose and duration of feeding. Treatments were divided into four treatment, P1 (no treatment), P2 (mice were induced with alloxan), P3 (mice were induced with alloxan and fed with fermented milk L. casei with 0.5 mL/mice) and P4 (mice were induced with alloxan and fed with Lactobacillus casei fermented milk 1 mL/mice). Provision of L. casei fermented milk provided at libitium and L. casei fermented milk given for 7 and 14 days. Blood were collected from Vena lateralis and dropped on the strip test Easy Touch GGHb. The results showed that not only dose administration of L. casei fermented milk had significantly decrease (P0.01) of glucose levels in mice, but also duration of treatment. It can be concluded that the administration of fermented milk L. casei can be used as a complement therapy for diabetic mice